New insights about the primary production dependence on abiotic factors: Ria de Aveiro case study. (November 2019) - Vaz, Leandro; Frankenbach, Silja; Serôdio, João; Dias, João M.
Highlights: The Delft-3D WAQ was successfully implemented for the first time in Ria de Aveiro. Primary production is maximum in the mid-channel areas, and minimum in river mouths. Seasonal variability of Ria de Aveiro's primary production is ruled by temperature. During spring and summer seasons, primary production is limited by nutrients. In winter, the nutrients are available for phytoplankton, but their metabolism rates are inhibited. Abstract: The Ria de Aveiro is a mesotidal coastal lagoon located in the north coast of Portugal. Although the biophysics of this coastal system has been extensively researched in previous studies, there is still a lack of knowledge about the fate of biomass of fluvial origin in the lagoon and on the on the limiting factors of growth of their plankton communities. Based on this assumption, this study presents a first attempt to perform an integrated assessment of the temporal and spatial evolution of water temperature, salinity, pH and chlorophyll a concentration in Ria de Aveiro lagoon, incorporating analysis of in situ data and numerical model predictions of local biophysics. Additionally, the influence of light availability, nutrient limitation and water temperature in lagoon's phytoplankton biomass was also evaluated. Water temperature, salinity, pH and chlorophyll a were measured in water samples collected monthly from February 2016 until February 2017, in 12 stations strategically located along the lagoon main channels. Chlorophyll a concentration was measured by extraction with aqueous acetone and quantified spectrophotometrycally. A model implementation based on Delft 3D suite was developed to simulate Ria de Aveiro hydrodynamics and water quality, and one-year simulation was performed including the sampling period. The results show a seasonal and longitudinal variability of the biophysical variables under analysis, allowing its quantification under different conditions in such a complex system. Particularly, the phytoplankton biomass showed a typical seasonal variability, characterized by a spring/summer bloom with a maximum of 8 μg/L, when environmental conditions are suitable to their growth, in opposition to nutrients concentration, that shows a 90% uptake of the total available by the phytoplankton communities. During these periods, Ria de Aveiro lagoon was found to be nutrient limited. Despite the seasonal light limitation, the primary production is strongly ruled by water temperature and nutrients concentration variability. These are strongly dependent on the riverine input, which is the most important natural source controlling the water temperature and nutrients concentration variability. The spatial and temporal distribution of the different variables is strongly influenced by the tidal dynamics, but also by geomorphologic features, such as depth and narrowness of the channels, which play therefore a major role in water quality characteristics. In summary, the water temperature establishes the seasonal variability, limiting photosynthesis in winter to values close to 0, while nutrients concentrations rule the primary production during spring and summer, since the nutrients uptake by phytoplankton and other marine organisms is about 90% higher than the replenishment from oceanic and riverine origin. These conclusions upgrade the state of the art about local processes, which generally referred that plankton community's growth in Ria de Aveiro is nutrients limited.